2021
DOI: 10.1021/acs.energyfuels.1c02240
|View full text |Cite
|
Sign up to set email alerts
|

Half-Pancake Bonding in Asphaltenes

Abstract: Aggregation of asphaltenes in petroleum crude oil is a well-known and ongoing problem for petroleum production. Asphaltenes aggregate even in situations where polycyclic aromatic hydrocarbon (PAH) model compounds do not, which implies that there is more to the phenomenon than just π-stacking. Half-pancake bonds involving stable radical PAH have been hypothesized to contribute to asphaltene aggregation (ZhangY. Zhang, Y. Energy Fuels20203490949107). We report density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Nevertheless, interactions between stable radicals, heteroatoms, and polar groups may contribute to aggregation. 98 The implication of localized π-radicals in the formation of π-stacking interactions of radical PAHs as soot precursors has also been investigated. 99 Martin et al 99 found that the σradicals are most reactive and form bonds with other radicals, while partially saturated pentagonal rings form localized πradicals which are highly reactive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, interactions between stable radicals, heteroatoms, and polar groups may contribute to aggregation. 98 The implication of localized π-radicals in the formation of π-stacking interactions of radical PAHs as soot precursors has also been investigated. 99 Martin et al 99 found that the σradicals are most reactive and form bonds with other radicals, while partially saturated pentagonal rings form localized πradicals which are highly reactive.…”
Section: Discussionmentioning
confidence: 99%
“…For this, a theoretical systematic investigation of the molecular orbitals and stability of the three different radicals proposed by Zhang et al (phenalenyl type π-radicals, doubly benzylic radicals, and benzylic radicals) would be necessary. With this objective in mind, recently Janesko and Brothers have reported density functional theory calculations on half-pancake bonding in asphaltene model compounds, finding that that half-pancake bonding alone is too weak and rare to drive asphaltene aggregation. Nevertheless, interactions between stable radicals, heteroatoms, and polar groups may contribute to aggregation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While asphaltenes form nanoaggregates at a low concentration in toluene, pyrene and alkylpyrene model compounds do not. , Heteroatoms and persistent organic radicals have been hypothesized to play important roles in asphalene aggregation. We recently used DFT simulations to address one specific hypothesis about the role of radicals in aggregation …”
Section: Resultsmentioning
confidence: 99%
“…We recently used DFT simulations to address one specific hypothesis about the role of radicals in aggregation. 92 In this section, we explore how simulations of asphaltenes imaged by nc-AFM can give insight into the "parts" of the structures that may be involved in aggregation and interfacial activity. We focus on variations in computed surface electrostatic potentials V s .…”
Section: Solvation and Intermolecularmentioning
confidence: 99%